PELATIHAN PERANCANGAN PICTOGRAM PADA SMA SWASTA AMAL BAKTI MABAR - Darma, Surya; John; Ibni Aura Sasabela (LPPM Universitas Potensi Utama, 2023)
The activities carried out at SMA Amal Bakti Mabar are a form of training activities on how to design pictograms that attract the attention of the audience in public places. The purpose of our activities is to foster interest in designing from students, especially in Medan City so as to foster creativity in them. We also conducted data analysis of this training activity using the 5W+1H method. This activity after being analyzed with this method, it turns out that participants can understand a little about how to design pictograms that are interesting and useful for public facilities. Through this pictogram design training, it is hoped that it can foster the interest and talent of art and design from these students. Keywords: 5W+1H analysis method; designing ;pictogram;